Karakteristik kematangan beberapa jenis sagu (Metroxylon sagu sp) siap panen menurut pemahaman masyarakat kampung Randawaya distrik Teluk Ampimoi kabupaten Kepulauan Yapen provinsi Papua - Arnolis Ruamba; Agus Irianto Sumule (Agrotek, 2020)
The purpose of this study was to study the maturity characteristics of several types of sago (Metroxylon sago sp) ready to harvest according to the Randawaya community, Kepulauan Yapen Regency. This research can give useful information for stakeholders in identifying the natural maturity of sago. This research was conducted using a descriptive method with a qualitative approach. From the results of interviews with the community, there are three stages of maturity of sago ready to harvest, such as: the early ripening phase which is marked by the opening of sago midrib, and the sago shoots shortening with the starch content is still low; the ripe phase which is marked by the midrib wrapping up to release shoots resembling a stump, and the starch is very dense; the late-ripe phase is characterized by the appearance of fingers resembling deer antlers and the sago sheath begins to wear off with the starch content of sago begins to decrease.